"To Gaze on the Beauty of the Lord": The Evangelical Resistance and Retrieval of Contemplation. Issue 1 (May 2014) - Schwanda, Tom
The term "contemplation" has played a significant role in the history of Christian spirituality. Regardless of the tradition, whether Roman Catholic, Orthodox, or Protestant, contemplation has been valued. Recently, however, some Evangelicals have raised various concerns about contemplation, including its Roman Catholic origin, the tendency to devalue Jesus Christ and his atonement, the marginalization of Scripture, and the assertion that a person who seeks to grow in the contemplative life will no longer be active to witness to the gospel in the world. This article while recognizing the potential for possible theological distortions argues that there is a biblical and theologically accurate manifestation of contemplation. In particular, this essay seeks to examine the presence of contemplation within the Evangelical church. To that end, the writings of four Americans representative of the beginning of eighteenth-century Evangelicalism are examined to discern whether they display a biblical and orthodox expression of contemplation. In all cases, whether male or female, Calvinist or Wesleyan, this quartet of spiritual leaders reveal and challenge contemporary Christians of all traditions to be more intentional about cultivating a loving and grateful gazing on God and desire to delight in and enjoy God more fully.